Natural Compounds in Non-Melanoma Skin Cancer: Prevention and Treatment - Kowalski, Szymon; Karska, Julia; Tota, Maciej; Skinderowicz, Katarzyna; Kulbacka, Julita; Drąg-Zalesińska, Małgorzata (Molecules (Basel, Switzerland), 2024)
The elevated occurrence of non-melanoma skin cancer (NMSC) and the adverse effects associated with available treatments adversely impact the quality of life in multiple dimensions. In connection with this, there is a necessity for alternative approaches characterized by increased tolerance and lower side effects. Natural compounds could be employed due to their safety profile and effectiveness for inflammatory and neoplastic skin diseases. These anti-cancer drugs are often derived from natural sources such as marine, zoonotic, and botanical origins. Natural compounds should exhibit anti-carcinogenic actions through various pathways, influencing apoptosis potentiation, cell proliferation inhibition, and metastasis suppression. This review provides an overview of natural compounds used in cancer chemotherapies, chemoprevention, and promotion of skin regeneration, including polyphenolic compounds, flavonoids, vitamins, alkaloids, terpenoids, isothiocyanates, cannabinoids, carotenoids, and ceramides.